Evaluation of Turkish Ophthalmologists’ Opinions on Surgical Waste During Cataract Surgery - Bahadır Utlu; Betül Dertsiz Kozan; Yunus Emre Erat (Journal of Ophthalmology)
Conclusion: In conclusion, most ophthalmologists agree that a lot of waste is generated during surgery and that more widespread use of sterilizable materials rather than disposables could reduce waste.